Principio de autonomía de la voluntad e instrumentos de carácter internacional en el sistema jurídico colombiano (2009)
The irruption of International Business Law (IBL) or the Uniform International Trade Law has produced a series of “waves” in theColombian legal system. It has been attributed to the private autonomy of the will, as a principle protected by IBL, the authority to replace the government power of protecting the interests of society. However, despitethis principle has existed for centuries, currently it has been subject ofreinterpretation. This paper will specifically approach the ‘Reconstruction’of this principle from the jurisprudence of the Colombian ConstitutionalCourt perspective and from the academic proposal of the Colombian Professor Diego Eduardo Lopez Medina